The Influence of QRIS User Convenience, Trust, and Risk on User Satisfaction QRIS for Students - Umara, Ruri Prastita; Suwandi, Djoko (Proceedings International Conference on Education Innovation and Social Science, 2023)
The aims of this study were to determine: 1) The effect of user convenience on QRIS user satisfaction; 2) The effect of user trust on QRIS user satisfaction; 3) Effect of user risk on QRIS user satisfaction; 4) ) Effect of user convenience, user trust, and user risk on QRIS user satisfaction. This research is a type of quantitative research using a survey research design with 70 respondents who were taken using a purposive sampling technique. The data analysis technique used is multiple linear regression analysis, t test, f test, coefficient of determination, relative contribution, effective contribution. The results of this study obtained the regression equation Y = 4.223 + 0.130X1 + 0.210X2 + 0.429X3. The results of the study show that: 1) user ease has a positive and significant effect on user satisfaction, knowing that based on the calculations obtained t count > t table, namely 2.981 > 1.994; 2) user convenience has a positive and significant effect on user satisfaction with the knowledge based on the calculations obtained t count > t table, namely 2.038 > 1.994; 3) user convenience has a positive and significant effect on user satisfaction, which is known on the basis of the calculations obtained t count > t table, namely 4.316 > 1.994; 4) user convenience, user trust, and user risk have a simultaneous effect on QRIS user satisfaction. Based on the calculation of the F test, the value of f count > f table is 36.989> 2.74.